Optimizing Bioaugmentation for Pharmaceutical Stabilization of Sewage Sludge: A Study on Short-Term Composting Under Real Conditions - Gabriela Angeles-De Paz; Juan Cubero-Cardoso; Clementina Pozo; Concepción Calvo; Elisabet Aranda; Tatiana Robledo-Mahón (Journal of Fungi)
A significant concentration of pharmaceuticals has been detected within composted sewage sludge. Their uncomplete removal and lack of monitoring during composting neglects their potentially toxic effects when used as a soil organic amendment. Previously, we successfully implemented a bioaugmentation–composting system focused on toxicity and pharmaceuticals’ concentration reduction. This method, however, comprised a long inoculant-acclimatization period, making it an unprofitable technology. Hence, this work aimed to explore a shorter and yet effective composting process by simultaneously implementing the inoculation of a native microbial consortium and the fungus Penicillium oxalicum XD 3.1 in composting piles of sewage sludge and olive prunings. All the piles were subjected to frequent inoculation, windrow turning, and monitoring of the physicochemical and biological parameters. Additionally, both the bioaugmentation stability and pharmaceuticals degradation were evaluated through different analysis and removal rates calculations. One hundred days earlier than previous attempts, both bioaugmentation treatments achieved adequate composting conditions, maintained core native populations while improving the degrading microbial diversity, and achieved around 70–72% of pharmaceutical remotion. Nevertheless, only Penicillium inoculation produced favorable toxicity results ideal for organic amendments (acute microtoxicity and phytotoxicity). Thus, a shorter but equally stable and effective degrading bioaugmentation–composting with P. oxalicum was achieved here.